Hypovitaminosis A in two beef calves: case report in Buenos Aires province = Hipovitaminosis A en terneros de cría: reporte de caso en la provincia de Buenos Aires - Pachiani, Martina (2024)
Hypovitaminosis A is an uncommon disease in grazing livestock systems, as the primary source of precursors (carotenes) is fresh forage. However, under environmental circumstances predisposing to the development of poor-quality forage, vitamin A deficiency and associated clinical signs can occur. This article describes the clinical findings of hypovitaminosis A in two 2-months-old calves in beef herd in Ayacucho, Buenos Aires Province, in November 2023. Blindness was the only clinical sign observed in a beef herd. Low vitamin A concentration was detected in blood of affected and non-affected calves and their mothers ranging from 7.8 to 24.8 μg dL-1 in calves and from 15.5 to 28.9 μg dL-1 in cows (reference 25-35 μg dL-1 in calves and 40-50 μg dL-1 in adults), confirming the deficiency status of the herd. During gestation, dams were fed corn-harvested hay. This diet may have been a poor source of carotene, leading to reduced hepatic reserves of vitamin A in the calves at birth. Consequently, clinical signs may have occurred during the first few weeks when these reserves were depleted.